Strengthening Student Well-Being in the Digital Era Through Character Strengths: A Systematic Review - Anbiya, Bakti Fatwa; Budimansyah, Dasim; Maftuh, Bunyamin; Komalasari, Kokom (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to synthesize empirical evidence on the role of character strengths in strengthening student well-being in the digital era and to examine its implications for character education policy. Using a systematic literature review guided by the PRISMA framework, this study conducted identification, screening, and eligibility assessment processes, resulting in the inclusion of 26 peer-reviewed international articles published between 2011 and 2024 from Scopus, Web of Science, and ERIC databases. Data were analyzed through thematic synthesis to identify dominant digital risks, character strengths associated with well-being, and their functional roles. The findings indicate that digital risks do not exert deterministic effects on student well-being; rather, their impact is conditional and shaped by students’ character strengths. Self-regulation, hope, gratitude, perseverance, and critical thinking consistently emerged as key strengths that function as direct predictors, moderators, and mediators of student well-being. These findings highlight the importance of reframing character education from a moral–normative orientation toward a strength-based and evidence-informed approach. The study concludes that strengthening student well-being in the digital era requires sustained educational investment in character strengths as preventive psychological capacities that support adaptive digital engagement and flourishing.